PENGGUNAAN MODEL PEMBELAJARAN GUIDED INQUIRY DENGAN MULTIMEDIA DALAM PENINGKATAN PROBLEM SOLVING SKILLS IPA TENTANG PESAWAT SEDERHANA DI KELAS V SD NEGERI 2 KEBULUSAN TAHUN AJARAN 2016/2017 - Rifanti, Alifah; Suryandari, Kartika Chrysti; Salimi, Moh (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The Use of Guided Inquiry Model Using Multimedia in Improving Student?s Problem-Solving Skills in IPA About Simple Machine of SD Negeri 2 Kebulusan in The Academic Year of 2016/2017. The objectives of this research are to improve problem-solving skills of IPA about the simple machine for the fifth-grade students of SD Negeri 2 Kebulusan in the academic year of 2016/2017. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Subjects of the research were a teacher and 30 students of the fifth grade of SD Negeri 2 Kebulusan. Techniques of collecting data were a test and non-test technique. The validity of data in this research was analyzed using triangulation of sources and triangulation of technique. Data were analyzed using data reduction, data display, and drawing conclusion or verification. The results of this research show that the use of Guided Inquiry model using multimedia can improve problem-solving skills on IPA about simple machine for the fifth grade of SD Negeri 2 KebulusanKeywords: Guided Inquiry, multimedia, problem-solving skills Abstrak: Penggunaan Model Pembelajaran Guided Inquiry dengan Multimedia dalam Peningkatan Problem Solving Skills IPA Siswa tentang Pesawat Sederhana di Kelas V SD Negeri 2 Kebulusan Tahun Ajaran 2016/2017. Tujuan penelitian ini adalah meningkatkan problem solving skills IPA tentang pesawat sederhana di kelas V SD Negeri 2 Kebulusan menggunakan model pembelajaran Guided Inquiry dengan multimedia. Penelitian ini merupakan penelitian tindakan kelas kolaboratif. Subjek penelitian ini adalah guru dan siswa kelas V yang berjumlah 30 siswa. Teknik pengumpulan data menggunakan: observasi, wawancara, dan tes. Validitas data menggunakan triangulasi sumber dan triangulasi teknik. Analisis data melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penggunaan model pembelajaran Guided Inquiry dengan multimedia dapat meningkatkan problem solving skills IPA siswa.Kata Kunci: Guided Inquiry, multimedia, problem solving skills IPA